Using tailored eHealth programmes to stimulate primary health care professionals' lifestyle counselling guideline adherence - Lessons learned from the STAR project. (April 2023) - Hoving, Ciska; de Ruijter, Dennis; Smit, Eline S.
Abstract: Background: Although individually tailored eHealth programmes have shown to be effective in changing patient and citizen health behaviours, they have so far not been applied to lifestyle counselling guideline adherence in primary health care professionals beyond our STAR project. The programme aimed to support general practice nurses adhering to national smoking cessation counselling guidelines and showed encouraging positive impacts on both nurse and patient level. Objective: To identify lessons learned from our successful application of a tailored eHealth programme in primary health care. Methods: Triangulation of information from different sources collected throughout the project run time (e.g., project meetings, discussions with experts in the fields of computer tailoring, smoking cessation and professional education and interactions with general practice nurses). Results: We identify four lessons learned which developers and testers of tailored eHealth programmes in primary health care should consider, relating to 1) Choosing outcome measures, 2) Measuring outcomes, 3) Practical feedback application & Programme accessibility, and 4) Programme interaction. Practice implications: We share this information in the hope that we will see more applications of this promising intervention strategy – that can build on our work – in the future. Highlights: Primary health care professionals regularly provide lifestyle counselling. Tailored eHealth programmes can stimulate lifestyle counselling guideline adherence. No application was identified since our STAR project on smoking cessation counselling. We consider lessons learned in STAR to support further application of the strategy. Barriers relate to outcome measures, feedback, accessibility, and interaction.